PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI BERPRESTASI TERHADAP KOMITMEN ORGANISASIONAL GURU DI SMP NEGERI 1 SELOPURO KABUPATEN BLITAR - Cicik Susana (Universitas Islam Balitar, 2017)
This research is to know the influence of transformational leadership and achievement motivation toward organizational commitment of teacher in SMPN 1 Selopuro Blitar Regency. The research was conducted by questionnaire survey method at the teacher at SMPN 1 Selopuro Blitar Regency. Data collection was done by distributing questionnaires to respondents. Questionnaires were distributed to 43 teachers at SMPN 1 Selopuro Blitar. The analytical tool used is Multiple Linear Regression using 16.00 for windows application. The results showed that: 1) There was no positive and significant influence of transformational leadership on organizational commitment of teachers in SMPN 1 Selopuro Blitar Regency; 2) There is a positive and significant influence of achievement motivation on organizational commitment of teachers in SMPN1 Selopuro Blitar Regency; and 3) There is a positive and significant influence of transformational leadership and achievement motivation simultaneously to the organizational commitment of teachers in SMPN1 Selopuro Blitar Regency.